2011
DOI: 10.7705/biomedica.v31i2.310
|View full text |Cite
|
Sign up to set email alerts
|

Actividad inotrópica inducida por el derivado carbamacepina-alquino en un modelo de corazón aislado y perfundido a flujo constante

Abstract: 232Figueroa-Valverde L, Díaz-Cedillo F, López-Ramos M, et al. ARTÍCULO ORIGINALActividad inotrópica inducida por el derivado carbamacepina-alquino en un modelo de corazón aislado y perfundido a flujo constante Introducción. Existen pocos datos con respecto a los efectos de la carbamacepina y sus derivados en el aparato cardiovascular; además, el mecanismo molecular y su sitio de acción celular no son claros. Objetivo. Evaluar los efectos inducidos por el derivado carbamacepina-alquino sobre la presión de perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Contractile function was assessed by measuring left ventricular developed pressure (LV/dP), using a saline-filled latex balloon (0.01 mm, diameter) inserted into the left ventricle via the left atrium 16 . The latex balloon was bound to cannula which was linked to pressure transducer that was connected with the MP100 data acquisition system.…”
Section: Inotropic Activitymentioning
confidence: 99%
“…Contractile function was assessed by measuring left ventricular developed pressure (LV/dP), using a saline-filled latex balloon (0.01 mm, diameter) inserted into the left ventricle via the left atrium 16 . The latex balloon was bound to cannula which was linked to pressure transducer that was connected with the MP100 data acquisition system.…”
Section: Inotropic Activitymentioning
confidence: 99%
“…On the other hand, in the search for the molecular mechanism of in the biological effect produced by 4-Me-7-Ph-C on left ventricular pressure, some reports have indicated that some compounds can exert changes in left ventricular pressure [33,34], producing a positive inotropic effect through calcium channel activation [35][36][37]. For this reason, we determined the biological activity of 4-Me-7-Ph-C on left ventricular pressure using an isolated rat heart model in the absence or presence of nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…Contractile function was assessed by measuring left ventricular developed pressure (LV/dP), using a salinefilled latex balloon (0.01 mm, diameter) inserted into the left ventricle via the left atrium [18]. The latex balloon was bound to cannula which was linked to pressure transducer that was connected with the MP100 data acquisition system.…”
Section: Inotropic Activitymentioning
confidence: 99%